POLA PERESEPAN DAN RASIONALITAS PENGOBATAN PASIEN DIABETES MELITUS TIPE 2 DI RSUD SULTAN SYARIF MOHAMAD ALKADRIE PONTIANAK - Robiyanto, Robiyanto (Universitas 17 Agustus 1945 Jakarta, 2016)
The rational medication requires diabetes mellitus (DM) patients to receive the appropriate medication based on their clinical condition, which can be observed from parameters i.e. right indication, right patient, right drug and as little as possible side effect. The prevalence of DM cases in West Kalimantan was 0,8% (2013). The aim of this study was to know the prescribing profile and the rationality of medication DM type 2 patients which were treated at RSUD Sultan Syarif Mohamad Alkadrie Pontianak. This research was an observational study with cross-sectional design and data result was presented descriptivley. Results of the rationality of medication for right indication; right patient; right drug and alert of side effect were 56,52%; 100%; 95,65%; 100% consecutively. To sum up, the prescribing and rationality of medication for DM type 2 patients at RSUD Sultan Syarif Mohamad Alkadrie Pontianak are already appropriate with PERKENI guidelines 2011.